Customer Loyalty Through Satisfaction, Engagement, and Trust: A Study in Islamic Banking in South Sulawesi, Indonesia - Idris, Munadi; Sukma, Evie (Li Falah: Journal of Islamic Economics and Business, 2023)
Islamic banking emphasizes religiosity and psychological aspects to enhance customer loyalty and satisfaction. Engagement and trust are variables that encompass both aspects, yet they have not been extensively studied in the context of Islamic bank customers. This research aims to examine the effect of customer satisfaction on loyalty through customer engagement and trust in Islamic banks in South Sulawesi. This explanatory quantitative study utilizes primary data from 384 respondents who are Islamic bank customers, analyzed using SmartPLS 3. The results show that customer satisfaction has a positive and significant effect on customer loyalty, engagement, and trust. Customer engagement and trust also positively and significantly influence loyalty. Trust positively affects customer engagement. Another notable finding is that customer satisfaction positively influences loyalty through customer engagement and trust. The implications of this research provide valuable insights for Islamic banks in building customer loyalty by addressing the aspects of satisfaction, engagement, and trust.